Reconstruction and repair, using mini-plate and bone graft for persons living with HIV with giant cell tumor of long bone: retrospective analysis of a single-center experience - Biao Xu (BMC, 2021)
Abstract Background To evaluate the effect of reconstruction and repair, using a mini-plate and bone graft for HIV -positive patients with giant cell tumor of long bone. Methods We conducted a retrospective analysis of 12 HIV positive patients with giant cell tumor of long bone. A non-HIV-positive cohort of patients, matched for age, sex, and disease type, was selected as the control group. From June 2012 to August 2020, curettage by ultrasonic scalpel was performed in all patients, combined with min- plate and bone graft treatment. All patients were followed- up for 18 to 60 months. Limb function was evaluated, using the MSTS93 scoring system, and any examples of postoperative recurrence, distant metastasis, complications, MSTS93 score, and fracture prognosis were recorded. Results The mean age of HIV group was 43.5 years. The ratio of men to women was 11: 1. In all cases the histopathological diagnosis was clear, except the patients with primary malignant giant cell tumor of bone, including five, three, two, and two cases in the proximal tibia, distal femur, distal tibia, and talus, respectively. Following their surgery, all patients were followed up with an average of 31.24 ± 11.84 months. No local recurrence or pulmonary metastases were observed. Post-surgery, all the 12 patients showed good bone morphologic repair and reconstruction, good bone healing, good joint function, and no pathological fractures around their lesion. In the HIV group, one case of giant cell tumor in the proximal tibia showed mild articular surface collapse and mild valgus deformity of the knee joint but retained good joint function. The MSTS scores of excellent or good in the two groups comprised 83.3%, thus, there was no significant difference between them (P > 0.05). Compared with preoperatively, the MSTS scores in the HIV group were significantly improved, ranging from 7 to 11 points preoperatively to 24 to 27 points postoperatively; this difference was statistically significant (P < 0.05). Conclusion Reconstruction and repair, using a mini-plate and bone graft for HIV -positive patients with giant cell tumor of long bone can achieve satisfactory results. The mini- plate requires little space and is flexible during reconstruction and fixation, significantly reducing complications such as surgical site infection, as well as preserving joint function and avoiding amputation; therefore, it is a safe and effective treatment method.